PROBLEM-BASED WORKSHEET DEVELOPMENT IN THE MAKING OF LIQUID SOAP FOR LEMON PEEL (CITRUS LIMON) - Robiah Siti Hanifah; Neneng Windayani; Imelda Helsy (UIN Sunan Gunung Djati Bandung, 2021)
The experiment in making innovative products that have benefits for everyday life is one of the efforts to face the challenges of the 21st century. One of the innovative products related to the concept of colloids and which can be made easily by students is antimicrobial liquid soap. During its development, the experiment required worksheets to direct students to the concepts to be studied and make it easier for students to carry out experiments. As for answering the challenges of the 21st century, the experimental worksheets that are made must be able to construct students' critical and creative thinking skills. To achieve this goal, the experimental worksheet is arranged with problem-based learning stages. This study aims to describe the stages of the development of problem-based worksheets on the manufacture of antimicrobial liquid soap from lemon zest (Citrus limon) extract and to analyze the results of the validation test. The research method used is design based research (DBR) and literature. Worksheets are arranged through analysis and development stages. The design stage is replaced by the library method. The worksheets that are arranged have a display in the form of discourse and questions that are arranged based on the stages of problem-based learning. Based on the results of the validation test, an average rcount of 0.76 was obtained, which means that the worksheets prepared were valid and could be used in Basic Chemistry practicum on colloid material.